O Parque Nacional Serra de Itabaiana em Sergipe e a relação socioambiental com os moradores dos povoados do entorno - Souza, Igor Azevedo (2019)
National parks have manifested themselves as important spaces for obtaining socioenvironmental information, for the interaction between society and nature, and for understanding the challenges to the use of their natural resources. The objective of the present study was to understand the socioenvironmental representativeness of the Serra de Itabaiana National Park, located in Sergipe, Brazil, based on the relationship of the inhabitants of the surrounding villages, their management and the conservation targets established in their management plan and it is characterized as exploratory, descriptive and quantitative research. The methodology was the Socioenvironmental Survey to Standardize Studies on Attitudes in Communities Adjacent to Conservation Units of Integral Protection, specifically National Park in Brazil, which consists of three stages: 1) elaboration of a questionnaire to study attitudes, focused on socio-environmental research to be applied vilages located around conservation units; 2) development of a protocol for the application of the questionnaire and; 3) application of the questionnaire in the villages around the protect área. 706 residents of the 20 villages were interviewed, between May and August 2018. The socioeconomic results indicated 61.5% female, 62.04% were natural of the study region; 46.36% aged between 30 and 49 years; 56.23% attended incomplete primary education; 60.05% were married; 41.50% were farmers and 66.86% received up to 2 minimum wages. 90.23% of the interviewees have already heard about PARNASI; 54.11% never visited it 63.03% did not know to inform which organ administers the protect area; 56.94% of the interviewees agreed totally on the uncontrolled use of water; 67.42% fully agreed that the region's springs and rivers are drying up; 59.35% answered the Indifferent option regarding deforestation of the protected area; 40.79% disagreed totally about the collection of wood for domestic uses; 60.33% fully agreed on the collection of medicinal plants; 60.48% disagreed fully about the hunting in the region; 44.05% fully agreed, regarding the decrease of wild animals in the region; 82.57% fully agreed on the importance of the protected area; 89.94% disagreed fully about participation; 40.79% disagreed fully on the collaboration and 45.89% disagreed fully on the benefits of protected area. The present study pointed out the impartiality of the residents of PARNASI as to its representativeness, since the absence of participation and motivation, which may be related to the lack of knowledge about the socioenvironmental importance that the UC represents for the region.